2011
DOI: 10.1002/jor.21533
|View full text |Cite
|
Sign up to set email alerts
|

Passive mechanical properties and related proteins change with botulinum neurotoxin A injection of normal skeletal muscle

Abstract: Summary The effects of botulinum neurotoxin A on the passive mechanical properties of skeletal muscle have not been investigated, but may have significant impact in the treatment of neuromuscular disorders including spasticity. Single fiber and fiber bundle passive mechanical testing was performed on rat muscles treated with botulinum neurotoxin A. Myosin heavy chain and titin composition of single fibers was determined by gel electrophoresis. Muscle collagen content was determined using a hydroxyproline assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 26 publications
7
41
0
Order By: Relevance
“…Increased passive forces suggest more specifically that stiffness of the ECM may have increased. Such elevated ECM stiffness was reported recently for isolated rat muscle fiber bundles after BTX‐A injection . The increased intramuscular connective tissue content shown in the BTX group may explain this finding.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Increased passive forces suggest more specifically that stiffness of the ECM may have increased. Such elevated ECM stiffness was reported recently for isolated rat muscle fiber bundles after BTX‐A injection . The increased intramuscular connective tissue content shown in the BTX group may explain this finding.…”
Section: Discussionsupporting
confidence: 82%
“…On the other hand, our findings were obtained only 5 days after BTX‐A injection. Even so, similar effects on passive mechanical properties, as described by Thacker et al ., were obtained 1 month after injection, suggesting they remain over time. These investigators also indicated that the effects of BTX‐A on normal and spastic muscle may differ.…”
Section: Discussionsupporting
confidence: 82%
“…25 Homogenized protein solution was resuspended to 0.125 μg μl −1 protein (BCA protein assay, Pierce, Rockford, IL, USA) in a sample buffer consisting of 100 mmol l −1 DTT, 2% SDS, 80 mmol l −1 Tris-base pH 6.8, 10% glycerol and 0.01% w/v Bromophenol Blue. Samples were boiled (2 min) and stored at 80°C.…”
Section: Detailed Methodsmentioning
confidence: 99%
“…Subsequent to the intramuscular BoNT-A injection, alterations in the physiological and mechanical properties of muscle have been reported in various histological, mechanical, and medical imaging studies [711]. These modifications included decreases of muscle mass or muscle fiber cross-sectional area, a selective loss of fast-twitch muscle fibers, and changes in muscle fiber composition, sarcomere structure, and contractile proteins [10, 12, 13]. In electrophysiological studies following a BoNT-A injection, indications of progressive muscle denervation and reinnervation in the treated spastic muscles were shown through changes in compound muscle action potentials and increased muscle fiber jitter and density [3, 14].…”
Section: Introductionmentioning
confidence: 99%